An Analysis of English Textbook for Tenth Graders of Vocational High School in Indonesia - Ridho Praja Dinata (Universitas Batanghari Jambi, 2022)
This study aims to investigate (1) material completeness, includes a short interpersonal text, transactional text and functional text, (2) material depth, includes the exposure, retention and production, and 3) the life skill development, includes personal skills, social skills, academic skills and vocational skills. Within the scope of the current study, it was analyzed an English textbook used by the tenth graders of Vocational High School. The research method used in this study was descriptive qualitative following four systematic steps, namely deciding on the subject, referring the criteria of English textbook analysis, applying the criteria by using checklist and interview, and analyzing the textbook. The data were gathering in this research through the checklist and interview containing the criteria of textbook analysis. Â Checklist used to gain the early data then interview used to gain the data in depth from the participant. The data were analyzing in this research through impressionistic overview and depth evaluation. As expected, the current study found that that â€œBahasa Inggrisâ€ textbook has made the criteria of a good textbook in term of material completeness, which is fulfill a short interpersonal text, transactional text and functional text. In the material depth, it fulfills the exposure, retention and production.Â Whereas in life skill development, the textbook provides the personal skills, social skills, academic skills and does not fulfill the vocational skill.